Práticas discursivas publicitárias: as (im)possibilidades do dizer na produção dos sujeitos LGBTI+ - Melo, Felipe Ferreira de (2023)
This work aims to understand the relationships between advertising discursive practices and the production of LGBTI+ subjects under the prism of Foucauldian Discursive Studies. The research analyzes three advertisements aired in 2021: “Avon Conecta – #AvonTáOn”, “Burger King – Como explicar?”, and “Novos Beijos Icônicos – Mercado Livre”, from the following discursive question: “How do the advertising statements of the mentioned ads discursively produce LGBTI+ subjects?”. For this, the statements are taken in their instances of events and in the cutout of the enunciative series, to be related to other statements, in order to observe the relationships between the elements of these series and the way they signify, construct, produce meanings about and for LGBTI+ subjects. The analysis endeavor was articulated in three thematic paths: “Body: discursive surface”; “Split subject: pride x confession”; “Neoliberalism: who profits from being woke?”. Through these paths, we reflect on what it means, nowadays, to have advertising statements circulating for a large audience on different channels. Sexuality manifests itself, according to Foucault (1984), through historically constructed and determined cultural patterns, and society is responsible for reinforcing them. By mobilizing discourses aligned with the perspectives, desires, and demands of LGBTI+ subjects, we observe that statements of advertising materials are more carefully thought out by brands when they intend to access and engage niches inscribed in the so-called minoritized groups. We also observe that a discourse can: fix or destabilize regularities; shape and redefine subjectivities; and objectify and subjectify subjects and bodies, in a history erected from multiple temporalities and intense discursive disputes. At the core of our inquiries is the understanding of how subjectivities are formed, shaped, and sometimes redefined by advertising statements.